Copolymer architecture effects on the morphology and surface performance of epoxy thermosets containing fluorinated block copolymers. Issue 15 (3rd June 2014) - Zheng, Yaochen; Xue, Qingquan; Zhu, Lemin; Xin, Zhirong; Sheng, Yan; Ren, Wanzhong
ABSTRACT The architecture effects on phases and surface enrichment behaviors of epoxy nanocomposites containing fluorinated block copolymers are investigated by the incorporation of two novel copolymers composed of poly (2, 2, 2‐trifluoroethyl methacrylate) (PTFEMA) and poly (ε‐caprolactone) (PCL), PCL‐b‐PTFEMA and PTFEMA‐b‐PCL‐b‐PTFEMA, with identical molecular weight and composition. These fluorinated copolymers in epoxy display distinguished self‐assembled structures, as evidenced by dynamic laser scattering and scanning electron microscopy measurements. Static contact angle detection suggests that the nanocomposites display an obvious improvement in surface water repellency and a reduction in surface free energy. The enhancement in surface hydrophobicity is attributed to the enrichment of PTFEMA blocks at the nanocomposite surface and to the formation of the specific surface morphology, as confirmed by atomic force microscopy. The different architectures of the two block copolymers give rise to differences in phase‐structures, and the ultimate surface performances of composites. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 1037–1045